Implementing The Theory Of Multiple Intelligences In Teaching English As A Foreign Language In Algeria (case Study Of University Teachers Of English In Oum El Bouaghi And Batna Universities) - Houssam Eddine, Atrous; Charif, Ben Boulaid (جامعة الوادي - University of Eloued, 2021)
Abstract Abstract: This study aims at evaluating the use of Multiple Intelligences theory for teaching in order to bridge the gap between the theory and practice in the Algerian educational context. It seeks to explore the teachers’ perspectives regarding this theory through interviewing teachers of English as a Foreign Language from the universities of Batna and Oum el Bouaghi. An interview with 20 teachers from both universities was conducted to collect the needed data. The interview reveals the teachers’ positive attitude towards using the theory to improve education, and provided us with tangible methods of implementing the theory in teaching for better results. It also showed the barriers that the theory faces in the Algerian context such as the lack of technological expertise and equipment. Thus, we stated promising solutions to the issues we found. In order to implement the theory at hand, we must urge the instructors, syllabus designers and administration managers to reconsider teaching beneath a new light where this method is taken into consideration to cater for all kinds of learners. ملخص باللغة العربية: تهدف هذه الدراسة إلى تقييم إستعمال نظرية الذكاءات المتعددة في التدريس وذلك لخلق جسر بين النظري والتطبيقي في النظام الجزائري للتدريس. تهدف أيضا لإستكشاف مفاهيم المعلمين بخصوص هذه النظرية من خلال اجراء مقابلة مع مدرٍسي اللغة الإنجليزية كلغة أجنبية من جامعتي باتنة و أم البواقي. جرت المقابلة مع 20 أستاذ من الجامعتين لتحصيل البيانات اللازمة. كشفت المقابلة نظرة الأساتذة الإيجابية تجاه إستعمال النظرية لتحسين التدريس, وزودتنا بطرق قابلة للتطبيق لإستعمال النظرية في التدريس لتحصيل نتائج أحسن. وكذلك كشفت العراقيل التي تواجه تطبيق النظرية في الجزائر كنقص في الخبرة و الموارد التكنلوجية. ولذلك, ذكرنا حلول واعدة للإشكالات التي وجدنها. لتطبيق هذه النظرية, يجب أن نلح على المعلمين, ومصصمي المناهج الدراسية و مسيري الإدارات بإعادة النظر في نظم التدريس بالأخذ بعين الإعتبار هذه النظرية لتلبية احتياجات كافة أنواع أـساليب التعلم لكل المتعلمين.
Article
Keywords: Multiple Intelligences Theory ; English as a Foreign Language ; Theory and practice; نظرية الذكاءات المتعددة ; الإنجليزية كلغة أجنبية ; النظري والتطبيقي